Upaya Meningkatkan Aktivitas dan Hasil Belajar IPA melalui Model Pembelajaran Problem Based Learning - Doremma Gultom; Jusniar Jusniar; Masniahturofikoh Masniahturofikoh (Universitas Negeri Makassar, 2024)
This study aimed to described student activity and improved student learning outcomes by using Problem Based Learning (PBL) Model in class 8 SMP Negeri 15 Bintan on topic Simple Machine. This type of this research is Classroom Action Research ( CAR ). This research was conducted in 3 cycles. Each cycles consists of Planning, Implementation, Observation, and Reflection. The subjects were all students in grade 8 SMP Negeri 15 Bintan 2021/2022 school year, while the researcher act as teacher. Data collection techniques in this study were observation and tests... The result showed an increase in student leraning from cyle I, II, III. The results showed an increase in the activities and learning outcomes of students in science learning. This is indicated by the average percentage of student learning activities in the first cycle of 49%. Cycle II increased to 74%. Cycle III increased to 84%. Student learning outcomes also increase, this can be seen from the average value of the first cycle for the average knowledge value, which is 68. Learning outcomes increase in the second cycle, which is 83 and in the third cycle, which is 89. It is recommended to the teacher to use the Problem learning model. Based Learning in teaching science and other subjects as an alternative to increase the activities and learning outcomes of students.